The foundations of worldwide economic integration power, institutions, and global markets, 1850-1930 - Dejung, Christof; Petersson, Niels P.; ProQuest (Firm) (Cambridge : Cambridge University Press, 2013)
"Power, Institutions, and Global Markets -- Actors, Mechanisms and Foundations of World-Wide Economic Integration, 1850--1930 Christof Dejung and Niels P. Petersson The rapid expansion of world trade between 1850 and 1914, its difficult reconstruction during the 1920s, and its subsequent decline during the Great Depression are key themes in the current historiography of economic globalisation. But such scholarship has broadly focused on the changing volume of foreign trade between nation states, on macro-economic problems such as national tariff policies, and on the history of the advancement of transport and communication technologies. There have been very few discussion of global trade development between the 1850s and the 1930s from the perspective of economic actors below the nation-state level, which is to say actors conducting trading operations in everyday business life. Likewise, economic and business historians have broadly neglected the institutional framework both shaping and shaped by the enterprises involved in such everyday trade. Through such a shift of focus, the contributions in the present volume strongly suggest that in the late nineteenth and early twentieth centuries, global economic integration was far more than the result of supply and demand and ever more efficient means of transport and communications"--
Machine generated contents note: Preface Harold James; Introduction: power, institutions, and global markets - actors, mechanisms, and foundations of worldwide economic integration, 1850-1930 Christof Dejung and Niels P. Petersson; Part I. Legal Institutions and Private Actors: 1. Legal institutions and the world economy, 1900-30; 2. Against globalisation: sovereignty, courts, and the failure to coordinate international bankruptcies (1870-1940) Jerome Sgard; 3. Credit information, institutions, and international trade: the UK, US, and Germany, 1850-1930 Rowena Olegario; Part II. Colonial Markets and Non-Western Actors: 4. The London Stock Exchange and the colonial market: a study of internationisation and power Bernard Attard; 5. The London gold market, 1900-31 Bernd-Stefan Grewe; 6. The boundaries of Western power: the colonial cotton economy in India and the problem of quality Christof Dejung; 7. The colonised as global traders: Indian trading networks in the world economy, 1850-1939 Claude Markovits; 8. The international patent system and the global flow of technologies: the case of Japan, 1880-1930 Pierre-Yves Donze; Part III. World War I and the Consequences for Economic Globalisation: 9. Transnational cooperation in wartime: the international protection of intellectual property rights during the First World War Isabella Lohr; 10. The resilience of globalisation during the First World War: the case of Bunge & Born in Argentina Philip Dehne; 11. Global economic governance and the private sector: the League of Nations' experiment in the 1920s Michele d'Alessandro.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: International economic integration -- History; International trade -- History; International finance -- History; International economic relations -- History; Globalization -- Economic aspects -- History; Electronic books